1975
DOI: 10.1159/000251455
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Long Ultraviolet and/or Visible Light with Topical Dihydroxyacetone

Abstract: Dihydroxyacetone (DHA) chemically induces long ultraviolet (UV) and/or visible photoprotection into the stratum corneum as demonstrated by (a) long UV protection of albino rats which were psoralen-photosensitized to black fluorescent light and (b) sunlight protection of five patients with long UV and/or visible photosensitivity. Previously, DHA treatment of skin was considered to provide no protection against UV. For clinical use, the combination of DHA and lawsone (2-hydroxy-1,4-naphthoquinone) is preferred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…[4][5][6] Dihydroxyacetone offers 2-to 5-fold protection against UV-A. 6,7 Concentrations of DHA up to 15% provide up to 10-fold protection against PUVA-induced erythema, depending on concentration. 8 Bound DHA is also shed faster from psoriatic plaques than from uninvolved skin, the differential in DHA staining of psoriatic vs uninvolved skin being greatest at 72 hours.…”
mentioning
confidence: 99%
“…[4][5][6] Dihydroxyacetone offers 2-to 5-fold protection against UV-A. 6,7 Concentrations of DHA up to 15% provide up to 10-fold protection against PUVA-induced erythema, depending on concentration. 8 Bound DHA is also shed faster from psoriatic plaques than from uninvolved skin, the differential in DHA staining of psoriatic vs uninvolved skin being greatest at 72 hours.…”
mentioning
confidence: 99%
“…Conse quently, the voluminous information about SPF is of no value in judging what consti tutes a therapeutically effective PPF. For ex ample, DHA provided all-day protection to a patient with EPP who tolerated over 3 h sunlight before therapy, for a porphyrin pro tection factor of 'only' 2.4 [3], On the other hand, DHA increased the tolerance of a very sensitive patient from 5 to 90 min, thus providing a factor of 18.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of EPP pa tients [3], who react strongly at 390-420 nm [1], extends the therapeutic spectrum of DHA. It has been reported that DHA plus lawsone (2-hydroxy-l,4-naphthoquinone) does not protect psoriatic patients undergo ing PUVA therapy [1], One would not expect a dramatic effect, since the high-intensity PUVA lamps would exceed most of the screening action of DHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the brown pigment has little screening action against sunlight [19,20], DHA has been used as a cosmet ic supplement in conventional sunscreen preparations. The DHA reaction product provides a protection factor for 3 or 4 in rats subjected to PUVA conditions, and protects patients with erythropoietic protoporphyria against sunlight [21], When used with lawsone (2-hydroxy-l,4-naphthoquinone), the agent protects against several disorders involving sensitivity to UVA [22], Lawsone is employed to provide UVB protection; its orange-red color did not protect rats against PUVA conditions [21], Therefore, the brown skin color produced by DHA provides broad-spectrum protection against UVA and visible light.…”
Section: What Constitutes a Good Uva Screen?mentioning
confidence: 99%